Rearing of Mud Crab, Scylla tranquebarica Larvae with Different Stocking Densities - Gunarto Gunarto; Sulaeman Sulaeman (Journal Omni-Akuatika, 2017)
Mud crab (Scylla tranquebarica) is an important aquaculture species, especially in Southeast Asian Countries. However, the larval rearing of this species faces problems resulted in low survival caused not only by intensif canibalism but also by prolonged in larval rearing period. The stocking density during ealy life stages is proposed to influence  the crablet production in the larvae rearing tanks. The objective of this research was to evaluate the effect of stocking densities on larval stage development and crablet production of mud crab, S. tranquebarica. Four different initial stocking densities of larvae were tested using 200 L fibre glass tank, namely:  A). 30 ind,/L, B). 45 ind./L, C). 60 ind./L and D). 75 ind./L. Rotifer, Brachionus sp, and Artemia nauplii were  fed to the larvae with additional commercial diet. Water exchanged in the rearing tank was performed since 7 days post hatching (dph)  to 20 dph  at  a rate of 10 to 40%. Larvae from each experimental tank was sampled periodically (2 to 4 days interval) in order to calculate larvae population, larvae development index (LDI). Megalopa occurences index (MOI), and crablet production were also monitored. The result showed that the highest of LDI and MOI were obtained from  treatment B and D which were significantly different (P<0.05) to the other treatments. Furthermore, the highest of crablet production was obtained from treatment D = 495.3+22.48 ind./tank, which was significantly higher (P<0.05) compared to treatment A (48.5+4.94 ind./tank), treatment B (167.5+10.61 ind./tank) and treatment C (218.33+10.41 ind./tank). Therefore, the stocking density of 75 ind./L is optimum for mud crab S. tranquebarica larvae and recommended to be applied for commercial larvae production in hatchery. Keyword: Production, crablet, stocking density, larvae, Scylla tranquebarica